Functional nanomaterials for optoelectronics and other applications : proceedings of Symposium F, European Materials Research Society Fall Meeting 2003, Warsaw University of Technology, 15th-19th September 2003 - Łojkowski, Witold; Blizzard, John R. (Diffusion and defect data. Solid state phenomena, 2004)
Research and development in the field of nanomaterials - thin films, nanowires, nanocrystals and nanostructured bulk materials - has increased very rapidly during recent years. Especially significant has been research in which the structure is closely controlled at the nanometer level in order to achieve the desired functional properties. Important discoveries have been made, including quantum dots, confinement effects and super-emission, and the prospects for rapid development in these areas are very promising. The results of much of the basic research have been the basis of an astonishing rate of progress in microelectronics. It is therefore expected that the study and development of nanomaterials will provide a firm foundation for a major increase in the number of advanced technologies and for the development of new optoelectronics and photonic devices. The two main reasons for the novel properties of materials which have structural features in the nanometer size-range are confinement effects and interface effects. The study of interfaces is therefore of primordial importance in the development of new devices. The present book covers recent advances in the manufacture of nanostructured materials, such as nanocrystals, nanostructured ceramics, nanoparticles, polymer composites and nano-sized semiconductor structures, and explores the fascinating physical phenomena exhibited by these materials.